PANDUAN UNGGAH KARYA ILMIAH : Determinan Karakteristik Pemerintah Daerah Dan Temuan Audit BPK Terhadap Kinerja Keuangan Pemerintah Daerah - Pebriana Dwi Jayanti (2021)
This research aims to determine the effect of characteristic of the local government and BPK audit findings to the financial performance of the local government in the period 2017 - 2019. The type of this research is quantitative research that uses secondary data based on Local Government Financial Report. A sample of this research consisted of 81 local government districs and cities. Techniques analyzing data in this research used regression model selection test, classical assumption test, multiple linear regression, and partial hypothesis testing (t test). Based on the result of data analysis, it can be concluded that (1) size of local government has a positive significant effect on financial performance of the local government based on the independence and activity ratio, (2) dependence on the central government has no effect on financial performance of the local government, (3) government expenditures has a negative significant effect on financial performance of the local government based on the activity ratio, and the result of examination BPK RI is (4) BPK audit findings has no effect on financial performance of the local government.